Parental job loss, secondary school completion and home environment - Tamás Hajdu; Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
This study examines the effect of parental job loss on children's completion of secondary school and the mediating role of home environment in that effect. It uses rich survey data from Hungary on adolescents age 14 through 21, with detailed measures of parental employment and home environment. The study replicates the average negative effect found in the literature. No effect is found for families with a history of providing a cognitively stimulating home environment, but the negative effect is strong for other families. Home environment matters more than initial income in mediating the effect. The results highlight the protective nature of a cognitively stimulating home environment.
Keywords: J60; I20; 330; job loss; home environment; school completion